2015
DOI: 10.1038/srep08291
|View full text |Cite
|
Sign up to set email alerts
|

The expression and crystallization of Cry65Aa require two C-termini, revealing a novel evolutionary strategy of Bacillus thuringiensis Cry proteins

Abstract: The insecticidal crystal protein (Cry) genes of Bacillus thuringiensis are a key gene resource for generating transgenic crops with pest resistance. However, many cry genes cannot be expressed or form crystals in mother cells. Here, we report a novel Cry protein gene, cry65Aa1, which exists in an operon that contains a downstream gene encoding a hypothetical protein ORF2. We demonstrated that ORF2 is required for Cry65Aa1 expression and crystallization by function as a C-terminal crystallization domain. The or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 31 publications
1
16
0
1
Order By: Relevance
“…Another interesting example for this type of operon organization is the 118 kDa Cry65Aa1 toxin which reportedly requires two C-termini for crystallization [30]. The N-terminus of Cry65Aa1 resembles a typical three-domain Cry protein.…”
Section: Separate Crystallization Domain Orfmentioning
confidence: 99%
See 1 more Smart Citation
“…Another interesting example for this type of operon organization is the 118 kDa Cry65Aa1 toxin which reportedly requires two C-termini for crystallization [30]. The N-terminus of Cry65Aa1 resembles a typical three-domain Cry protein.…”
Section: Separate Crystallization Domain Orfmentioning
confidence: 99%
“…This downstream ORF was shown to be required for the efficient expression and crystallization of the Cry65Aa toxin. Peng et al [30] claimed that the unusual C-terminus of Cry65Aa is also required for crystallization, although this was not clearly demonstrated. Interestingly this report described how a stem-loop structure within the orf2 gene sequence can aid expression by stabilizing the cry65Aa mRNA.…”
Section: Separate Crystallization Domain Orfmentioning
confidence: 99%
“…Although its genome harbors four potential nematicidal cry genes, only two of the four have the ability to target nematodes, with the exception of the cancer cell-killing parasporin Cry65Aa1 (39). Based on an analysis of other strains, such as B. thuringiensis L366 with naturally truncated Cry5Ad1 (40); B. thuringiensis DB27 products Cry21Fa1, Cry21Ha1, and naturally interceptive Cry21Ga1 (6); and YBT1518 products Cry6Aa2, Cry55Aa1, and silent Cry5Ba2 (26), we believe that the different characteristic crystal proteins that exist in one Bt may be the result of coevolution between the host and pathogen (41) and that the outcome arises from the natural selection pressure of antagonist nematodes and Bt itself.…”
Section: Figmentioning
confidence: 99%
“…They demonstrated that the Cry2Aa production level was enhanced, but the increment did not exceed 15%. The variability of Cry2Aa production enhancement levels could mainly be due to differences in gene combination strategies …”
Section: Discussionmentioning
confidence: 99%